Plant Genes Related to Gibberellin Biosynthesis and Signaling Are Differentially Regulated during the Early Stages of AM Fungal Interactions - Ortu, Giuseppe (2016)
Dear Editor, Phytohormones are essential regulators of plant development, but their role in the signaling processes between plants and fungi during arbuscular mycorrhizal (AM) establishment is far from being understood (Ludwig-Müller, 2010). AM colonization leads to extensive effects on host metabolism, as revealed by transcriptome studies of AM plants (Hogekamp et al., 2011). Some genes have been specified as an AM core set, since they are mycorrhizal-responsive, irrespective of the identity of the plant, of the fungus, and of the investigated organ. These data support the idea that, on colonization, plants activate a wide reprogramming of their major regulatory networks and argue that mobile factors of fungal or plant origin are involved in such generalized metabolic changes. In this context, hormones may be good candidates (Bonfante and Genre, 2010). However, the emerging picture of the interaction between phytohormones and AMs is very patchy, and information on gibberellin (GA) involvement is still more limited (García-Garrido et al., 2010). The role of GA during nodulation is instead known to control the nodulation signaling pathway (Ferguson et al., 2011).